Heterogenous impacts of climate change on morbidity - Tamás Hajdu (Global Labor Organization (GLO), 2025)
This paper examines the effect of temperature on emergency department (ED) visits using administrative data covering 50% of the Hungarian population and 3.52 million ED visits from 2009 to 2017. The results show that ED visit rates increase when average temperatures exceed 10°C, primarily driven by mild cases that do not result in hospitalization. Higher humidity amplifies the heat effect, which is also stronger following consecutive hot days. The findings further indicate that the impacts of climate change - both present and future - are substantial. Between 2009 and 2017, 0.66% of the ED visits were attributed to temperature changes relative to the period 1950-1989. Furthermore, by the 2050s, compared to the first 15 years of the 21st century, the annual ED visit rate is projected to rise by 1.24%-1.70%, depending on the climate scenario. A heterogeneity analysis reveals that the effects of high temperatures and the future impacts of climate change are disproportionately greater in lower-income districts, areas with lower general practitioner density, and among younger adults.
Keywords: I10; I14; I18; Q54; 330; temperature; climate change; morbidity; emergency department visits; heterogeneous impacts